2020
DOI: 10.3329/bjms.v19i0.48171
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Aural Tick in a General Practitioner Setting During COVID-19 Lockdown

Abstract: Foreign body in the ear including beads and seeds is not uncommon in children. Tick also has been a common aural foreign body especially in tropical climate countries. Although in older cooperative children it can be attempted in the clinic setting, most of paediatric aural foreign bodies require general anaesthesia. In addition, a general practitioner setting may impose additional limitations. The available instruments and experience maybe be different from a tertiary referral centre. We report a case of a 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, worldwide dissemination of this information to health care professionals can assist with preventing COVID-19 infection. [18][19][20][21] On a single dental appointment dental experts can be exposed to all common courses for COVID-19 contamination (aerosols and droplets, contact with materials, dental sharp instruments, or contaminated surfaces), 22 and even when a procedure is finished, they are exposed because of the long period that pathogenic microorganisms remain suspended in the air. Confronting a pandemic situation, maxillofacial rehabilitation specialists associated with supportive care in cancer must rearrange dental clinical practice to take into consideration of care of patients contaminated with COVID-19 who require prosthodontic appliances.…”
Section: Workflow For the Fabrication Of Obturator Prostheses In The ...mentioning
confidence: 99%
“…Therefore, worldwide dissemination of this information to health care professionals can assist with preventing COVID-19 infection. [18][19][20][21] On a single dental appointment dental experts can be exposed to all common courses for COVID-19 contamination (aerosols and droplets, contact with materials, dental sharp instruments, or contaminated surfaces), 22 and even when a procedure is finished, they are exposed because of the long period that pathogenic microorganisms remain suspended in the air. Confronting a pandemic situation, maxillofacial rehabilitation specialists associated with supportive care in cancer must rearrange dental clinical practice to take into consideration of care of patients contaminated with COVID-19 who require prosthodontic appliances.…”
Section: Workflow For the Fabrication Of Obturator Prostheses In The ...mentioning
confidence: 99%
“…Most traumatic orthopedic surgeries are medium and short operations (1-2 hours) and thus typically involve brachial plexus block anesthesia with operations in the upper arms, shoulder joints and clavicles, or spinal anesthesia with operations in the lower extremities [1][2][3][4][5][6][7][8][9] . However, those techniques could not guarantee the absolute success rate even with the most experienced anesthetists and could be associated with a number of complications [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Foreign bodies among children less than 8-year-olds is commonly reported worldwide. There are several big sample size study done and it showed 75% children less than 8 years old 1,2,3,11 . There are a few common nasal foreign bodies include button, bead, buttons, small toy, candle, hard food, paper, cloth, and small button batteries 4,5,9 .…”
Section: Introductionmentioning
confidence: 99%